WASP-92b, WASP-93b and WASP-118b: three new transiting close-in giant planets. Issue 3 (20th August 2016) - Hay, K. L.; Collier-Cameron, A.; Doyle, A. P.; Hébrard, G.; Skillen, I.; Anderson, D. R.; Barros, S. C. C.; Brown, D. J. A.; Bouchy, F.; Busuttil, R.; Delorme, P.; Delrez, L.; et al.
Abstract : We present the discovery of three new transiting giant planets, first detected with the WASP telescopes, and establish their planetary nature with follow up spectroscopy and ground-based photometric light curves. WASP-92 is an F7 star, with a moderately inflated planet orbiting with a period of 2.17 d, which has R p  = 1.461 ± 0.077 R J and M p  = 0.805 ± 0.068 M J . WASP-93b orbits its F4 host star every 2.73 d and has R p  = 1.597 ± 0.077 R J and M p  = 1.47 ± 0.029 M J . WASP-118b also has a hot host star (F6) and is moderately inflated, where R p  = 1.440 ± 0.036 R J and M p  = 0.514 ± 0.020 M J and the planet has an orbital period of 4.05 d. They are bright targets ( V = 13.18, 10.97 and 11.07, respectively) ideal for further characterization work, particularly WASP-118b, which is being observed by K2 as part of campaign 8. The WASP-93 system has sufficient angular momentum to be tidally migrating outwards if the system is near spin–orbit alignment, which is divergent from the tidal behaviour of the majority of hot Jupiters discovered.